Study of Qattara depression and its hydropower potential - El Shafei, Aly (AUC Knowledge Fountain, 2017)
The Qattara Depression is a very interesting geomorphic feature that has been suggested to be used for hydropower production. This research will investigate hydrological elements affecting the water balance of the Qattara Depression region. Climatic data obtained from weather stations surrounding the region will be used in the investigation, as climatic factors such as rain and water evaporation would affect the mass balance equation. Then environmental and economic implications of such a project will also be studied. Many schemes have been suggested in the past for the project. All these schemes are compared economically in this work for the first time as far as the author knows. And the model employed investigates elements that had not been previously investigated. The outward seepage calculation and its affect on the plant lifetime is included in the model and the economic study and also its environmental impacts are checked. The effect of the channel flow of water before reaching the lowest point of the depression as it was not previously included in the evaporation calculation, but it is investigated in this model. Also a detailed study of the effect of the salinity increase of the water in the depression is investigated. The way all this enabled is by using data from three weather stations near Qattara Depression (Siwa, Dabaa, Wadi El Natroon) and the data is used on a monthly bases to calculate the evaporation that would occur as it would be used in the mass balance equation that includes the evaporation, that is affected by the progressive salinity increase, the inward and outward seepage, the rainfall, and the inflow from the sea. Using that calculation the progressive increase in the surface level in the depression is always obtained and the best design and economic study is planned accordingly.